2021
DOI: 10.3390/diagnostics11122344
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Red Cell Distribution Width/Albumin Ratio to Discriminate 28-Day Mortality in Critically Ill Patients with Pneumonia Receiving Invasive Mechanical Ventilation, Compared with Lacate/Albumin Ratio: A Retrospective Cohort Study

Abstract: The value of the red cell distribution width (RDW) is associated with prognosis in critically ill patients. A simplex combined index—the RDW/albumin ratio—has been proposed for the prediction of mortality, as has the lactate/albumin ratio. The aim of this study was to evaluate the clinical utility of the RDW/albumin ratio regarding 28-day mortality in critically ill patients with pneumonia. Clinical data of critically ill patients with pneumonia who were hospitalized in the medical intensive care unit from May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
4
15
1
Order By: Relevance
“…In addition, the authors reported that the 28-day mortality rate was significantly higher in patients with a RAR cut-off value of >5.73 than in patients with a RAR cut-off value of <5.73 (52.3% sensitivity, 79.2% specificity, and AUC: 0.688). 4 In our study, the RAR levels were found to be higher in patients who died and in those who received MV and vasopressor support than in those who survived and did not receive support (for all p< 0.001). Furthermore, when the RAR cut-off value is >5.43, it seems to be as powerful a parameter as RDW in estimating mortality with 91.6% sensitivity, 93.7% specificity, 93.1% NPV and 0.965 AUC values.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…In addition, the authors reported that the 28-day mortality rate was significantly higher in patients with a RAR cut-off value of >5.73 than in patients with a RAR cut-off value of <5.73 (52.3% sensitivity, 79.2% specificity, and AUC: 0.688). 4 In our study, the RAR levels were found to be higher in patients who died and in those who received MV and vasopressor support than in those who survived and did not receive support (for all p< 0.001). Furthermore, when the RAR cut-off value is >5.43, it seems to be as powerful a parameter as RDW in estimating mortality with 91.6% sensitivity, 93.7% specificity, 93.1% NPV and 0.965 AUC values.…”
Section: Discussionsupporting
confidence: 45%
“…Serum albumin is a laboratory marker that can be routinely measured in blood; it is an acute phase reactant, a protein that plays a role in the control of oncotic pressure and one that has antioxidant properties. 4 In addition, albumin has been shown to be an inflammation marker. 13 , 30 In the studies of Chen and Takegawa et al, the albumin levels were emphasized to be a prognostic factor in patients with pneumonia or sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, RAR has been gradually found to be associated with mortality from acute respiratory distress syndrome, 16 stroke, 13 severe pneumonia, 15 and heart failure. 33 However, few studies have shown that RAR is related to the mortality of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Given this, we conjecture that RAR is a negatively correlated indicator of COPD prognosis. Previous studies have also indicated that RAR is associated with mortality in patients with stroke, 13 diabetes, 14 severe pneumonia, 15 and acute respiratory distress syndrome. 16 However, there are few studies that explore the relationship between RAR and the prognosis of COPD patients.…”
Section: Introductionmentioning
confidence: 95%